Perhitungan Tingkat Keausan Piston dan Oversize Piston Mesin Diesel - Andrian, Feri; Suyanto, Suyanto (Marine Science and Technology Journal, 2023)
The cylinder in the internal combustion engine is one of the main parts, where this part is where the piston works. Due to the importance of the piston and cylinder functions in the combustion process in diesel engines, it is necessary to have a good maintenance schedule, as well as repairs to overcome existing problems. Among the things that can be done if the piston and cylinder damage is severe is to replace the piston (oversize). This study aims to identify wear problems on the cylinder liner and piston of diesel engines. Measurement of cylinder liner clearance is carried out to determine wear and tear by comparing it with the initial standard diameter. The piston diameter measurement is carried out to determine its wear by comparing it with the initial standard diameter size. The biggest wear occurs in cylinder liner number 4 which is 0.42 mm. After measuring the diesel engine with 6 cylinders, the largest wear result was obtained on cylinder liner number 4, which was 0.42 mm. The biggest piston wear occurs on piston number 1 which is 0.65mm. Need to oversize almost all cylinders except for cylinder number 2.